ANALISIS PKOR WAY HALIM SEBAGAI RUANG PUBLIK BERKELANJUTAN BERDASARKAN POLA PERILAKU - Guruh Kristiadi Kurniawan; Citra Devita; Muhammad Arya Guna Akbar (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: Public spaces are often considered merely as facilities that provide space for user activities/interactions, resulting in minimal awareness regarding the maintenance and supervision of the available space. In its formation, public spaces must also support sustainability in each of its elements that link environmental aspects (space) with social aspects (users) to fulfill needs and complement each other. In response to this, PKOR Way Halim as a provider of public space needs to be analyzed to make adjustments in accordance with sustainable public space criteria. The method employed is a qualitative descriptive method focusing on behavior patterns through behavior mapping, which is then analyzed by elaborating on the understanding related to sustainability. Thus, the results indicate that PKOR Way Halim as a provider of public space does not yet meet the